Letter: irritable bowel syndrome—how a low‐FODMAP diet or yoga might help. Issue 3 (8th January 2018) - Uno, Y.
Abstract : Linked Content This article is linked to Schumann et al and Schumann and Cramer papers. To view these articles visit https://doi.org/10.1111/apt.14400 and https://doi.org/10.1111/apt.14457 .